Burdens of proof cryptographic culture and evidence law in the age of electronic documents - Blanchette, Jean-Franđcois (MIT Press, 2012)
This work provides an examination of the challenges of establishing the authenticity of electronic documents - in particular the design of a cryptographic equivalent to handwritten signatures.
Keywords: Electronic evidence.; Data encryption (Computer science) -- Law and legislation.; elektronické knihy; electronic books